1991
DOI: 10.1093/jat/15.6.323
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Abbott ADx Amphetamine/Methamphetamine II Abused Drug Assay: Comparison to TDx, EMIT, and GC/MS Methods

Abstract: Although the legitimate clinical use of amphetamine and amphetamine congeners is declining, the illicit use of these drugs remains high. There is a need for a rapid and conclusive method for detecting these compounds in routine urine drug testing, drug screening in drug rehabilitation centers, and as an aid in the diagnosis and treatment of potential overdoses. The Abbott ADx Amphetamine/Methamphetamine II assay (A/M II), a fluorescence polarization Immunoassay (FPIA), was compared to the Abbott TDx Amphetamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…AS shown in Table III, in the presence of amphetamine, there was an enhanced response for methamphetamine in the sample. This enhancement effect in the presence of a combination of amphetamine and methamphetamine has also been reported in the Abbott assay for amphetamine (13,14). Baker and colleagues (15) have evaluated the Abuscreen ONLINE assay for amphetamines on the Hitachi 737.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…AS shown in Table III, in the presence of amphetamine, there was an enhanced response for methamphetamine in the sample. This enhancement effect in the presence of a combination of amphetamine and methamphetamine has also been reported in the Abbott assay for amphetamine (13,14). Baker and colleagues (15) have evaluated the Abuscreen ONLINE assay for amphetamines on the Hitachi 737.…”
Section: Discussionmentioning
confidence: 54%
“…It contains mouse amphetamine and methamphetamine monoclonal antibodies, which, however, cannot give a positive result if only methamphetamine is present in urine. It has been reported that methamphetamine in the presence of amphetamine enhanced the reaction and gave a response in the assay that was greater than the sum of their concentrations (8). This study was undertaken to determine if, and to what extent, the newest amphetamine analogues, MDEA and ethylamphetamine, cross-react with Roche Abuscreen ONLINE amphetamine immunoassays.…”
Section: Introductionmentioning
confidence: 99%
“…Although some vari abil ity exists in ana lytes detected or inter fer ing ana lytes that can pro duce false-positive tests, many stud ies, in addi tion to ours cited above, have shown that most immu no as say screen ing meth od olo gies are simi lar when used appropri ately. [3][4][5][6][7][8][9][10][11][12][13] There is not the marked dif fer ence suggested by Ramey et al The sta tis ti cal meth od ol ogy used by Ramey et al, in an attempt to sup port their conten tion that FPIA is supe rior to EMIT, is flawed. They have com pared screen ing results fol lowed by GC/MS con fir ma tion obtained from one set of sub jects using EMIT (Table II) with a dif fer ent set of sub jects who had only FPIA (Table III) test ing with no GC/MS con fir mation.…”
Section: Urine Drug Screeningmentioning
confidence: 99%
“…Immunoassays have been evaluated for the detection of amphetamines in urine (286)(287)(288). Amphetamines were determined indirectly by atomic absorption spectrometry (AAS) on the basis of their reaction with CS2 to yield dithiocarbamic acids (289).…”
mentioning
confidence: 99%